Andromeda XXV – a dwarf galaxy with a low central dark matter density. Issue 3 (14th March 2023) - Charles, Emily J E; Collins, Michelle L M; Rich, R Michael; Read, Justin I; Kim, Stacy Y; Ibata, Rodrigo A; Martin, Nicolas F; Chapman, Scott C; Balbinot, Eduardo; Weisz, Daniel R
ABSTRACT: Andromeda (And) XXV has previously been reported as a dwarf spheroidal galaxy (dSph) with little-to-no dark matter. However, the uncertainties on this result were significant. In this study, we nearly double the number of member stars and re-derive the kinematics and mass of And XXV. We find that And XXV has a systemic velocity of νr = −107.7 ± 1.0 kms −1 and a velocity dispersion of σ _ν =3.7^+1.2_-1.1 kms −1 . With this updated velocity dispersion and a new literature measurement of the radial surface brightness profile, we derive a mass contained within the half-light radius of M(rr_h)=4.7^+3.0_-2.9× 10^6 M⊙ . This mass corresponds to a mass-to-light ratio of [M/L]_r_h=25^+17_-16 M⊙ /L⊙, demonstrating that And XXV is most-likely dark matter dominated. We also measure the metallicity of And XXV to be [Fe/H]=-1.9± 0.1 dex, which is in agreement with previous results. Finally, we extend the analysis of And XXV to include mass modelling using GravSphere . We find that And XXV has a low central dark matter density, ρDM (150 pc) = 2.3^+1.4_-1.1× 10^7 M⊙ kpc −3, which makes And XXV a clear outlier when compared to other local group dSphs of the similar stellar mass. In a companion paper, we will explore whether some combination of dark matter cusp-core transformations and/or tides can explain And XXV's low density.